1988
DOI: 10.1073/pnas.85.20.7790
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by cAMP and vasoactive intestinal peptide of phosphorylation of specific proteins in striatal cells in culture.

Abstract: We have studied three low molecular weight phosphoproteins, ARPP-16, ARPP-19, and ARPP-21 (cAMPregulated phosphoproteins of Mr 16,000, 19,000, and 21,000, respectively) in reaggregate cultures from various regions of fetal mouse brain. ARPP-16 and ARPP-21 were detected only in striatal and cortical cultures. In contrast, ARPP-19, which is structurally related to ARPP-16, was also present in reaggregate cultures prepared from thalamus and ventral and dorsal mesencephalon, as well as in monolayer cultures of ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 27 publications
(22 reference statements)
3
34
0
Order By: Relevance
“…Therefore ARPP-21 was measured by in vitro phosphorylation with the catalytic subunit of cAMP-dependent protein kinase (a gift of A. C. Nairn) and [-32P]ATP followed by immunoprecipitation with a specific antiserum (G154) as described (20). Comparison of data obtained from immunoblots and phosphorylation/immunoprecipitation for ARPP-16, ARPP-19, and DARPP-32 showed that the two methods gave similar results (data not shown).…”
mentioning
confidence: 78%
“…Therefore ARPP-21 was measured by in vitro phosphorylation with the catalytic subunit of cAMP-dependent protein kinase (a gift of A. C. Nairn) and [-32P]ATP followed by immunoprecipitation with a specific antiserum (G154) as described (20). Comparison of data obtained from immunoblots and phosphorylation/immunoprecipitation for ARPP-16, ARPP-19, and DARPP-32 showed that the two methods gave similar results (data not shown).…”
mentioning
confidence: 78%
“…Involvement of protein phosphatases in the regulation of neuronal currents by 5-HT and cAMP has also been reported in Aplysia californica (21). The reduced phosphatase activity that we induced with 8-Br-cAMP or 5-HT could have resulted from a sustained activity of cAMP-regulated phosphatase inhibitors, such as protein phosphatase inhibitor 1 or the 32-kDa dopamine-and cAMP-regulated phosphoprotein (DARPP-32), that are highly expressed in colliculi neurons (20,(22)(23)(24). How the sustained activity of these inhibitors could be maintained after the transient activation of PKA remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that phosphorylation of in the choroid plexus of the rat is regulated by norepinephrine and 5-HT (Snyder et al, 1992) and that DARPP-32 therefore may play a role in the control of secretion of cerebrospinal fluid. An increase in phosphorylation of striatal ARPP-21, ARPP-19, and ARPP-16 by vasoactive intestinal peptide in vitro has also been demonstrated (Girault et al, 1988).…”
Section: Functional Implicationsmentioning
confidence: 96%